The Effect of Antimony in the Intermediate IrO2-SnO2-Sb2O5 Oxide Layer on Titanium Substrate for Oxygen Evolution Mn1-x-yMoxSnyO2+x Anodes in Seawater Electrolysis - Bhattarai, Jagadeesh (Journal of Nepal Chemical Society, 2009)
An attempt is made to find out the optimal compositions for the intermediate oxide layer of IrO2-SnO2-Sb2O5 in preventing insulating titanium oxide formation on titanium substrate for the oxygen evolution Mn1-x-yMoxSnyO2+x anodes in electrolysis of 0.5 M NaCl of pH 1 at 1000 A.m-2. Effects of antimony and iridium in the intermediate IrO2-SnO2-Sb2O5 layer are discussed. The 75 % of the iridium content in the intermediate layer of the oxygen evolution anodes can be substituted by SnO2 and small amount of Sb2O5 to increase the electronic conductivity of the intermediate layer as well as the activity of the Mn1-x-yMoxSnyO2+x/IrO2-SnO2-Sb2O5/Ti anodes for seawater electrolysis at pH 1. Although Sb5+ addition is effective in decreasing the Ir4+ concentration in the intermediate layer of the anodes, the Ir1-x-ySnxSbyO2+0.5y intermediate layers with the Sb5+/Sn4+ between 0.125-0.285 in the coating solution showed excellent performance of the oxygen evolution efficiency. All the examined manganese-molybdenum-tin triple oxides, Mn1-x-yMoxSnyO2+x, prepared by anodic deposition on the IrO2-SnO2-Sb2O5-coated titanium substrate showed around 99% initial oxygen evolution efficiency at a current density of 1000 A.m-2 in 0.5 M NaCl of pH 1 at 25ºC. Keywords: global CO2 recycling, hydrogen production electrode, IrO2-SnO2-Sb2O5 layer, 0.5 M NaCl, titanium substrate. DOI: 10.3126/jncs.v23i0.2093 J. Nepal Chem. Soc., Vol. 23, 2008/2009 Page: 21-32